Case report of thrombotic thrombocytopenic purpura with severe acquired ADAM TS 13 deficiency in a previously healthy adult male - Joseph, Jimmy (International Journal of Advances in Medicine, 2025)
This was a 23 years old, previously healthy male, who presented with status epilepticus, fever and hematuria. Peripheral blood smear showed severe hemolytic anemia and thrombocytopenia. Thrombotic thrombocytopenic purpura (TTP) was suspected and treatment initiated with therapeutic plasma exchange and corticosteroids following which patient showed minimal improvement. Subsequently, blood reports showed critically low ADAM TS 13 activity, which confirmed the diagnosis of TTP. Plasmapheresis was continued along with methyl prednisolone and Rituximab, following which patient showed considerable clinical improvement.